2018
DOI: 10.1177/1934578x1801301023
|View full text |Cite
|
Sign up to set email alerts
|

12-Hydroxycorniculatolide a from the Mangrove Tree, Lumnitzera littorea

Abstract: A new macrocyclic lactone, 12-hydroxycorniculatolide A (1), along with three known compounds, corniculatolide A (2), 12-hydroxy-11-O-methylcorniculatolide A (3) and 6,7-dimethoxycoumarin (4) were isolated from the methanolic extract of the twigs of Lumnitzera littorea. All compounds were characterized using spectroscopic methods. All compounds were screened against a panel of six Gram positive and five Gram negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The accumulation of sulfates may be organ-specific. In case of the investigated Lumnitzera species, they are found in the roots, which normally are in contact with sea water, while they were not reported from studies on leaves and twigs [26,[29][30][31]. In this study, both species showed similar patterns of sulfated metabolites despite L. littorea is predominantly occurring at well-drained sites with less salinity, and typically growing as a tree, while L. racemosa is more resistant to saline conditions and occurs at the margin of bare salt pans [70] often growing as a shrub.…”
Section: Phytochemcial Analysesmentioning
confidence: 87%
See 1 more Smart Citation
“…The accumulation of sulfates may be organ-specific. In case of the investigated Lumnitzera species, they are found in the roots, which normally are in contact with sea water, while they were not reported from studies on leaves and twigs [26,[29][30][31]. In this study, both species showed similar patterns of sulfated metabolites despite L. littorea is predominantly occurring at well-drained sites with less salinity, and typically growing as a tree, while L. racemosa is more resistant to saline conditions and occurs at the margin of bare salt pans [70] often growing as a shrub.…”
Section: Phytochemcial Analysesmentioning
confidence: 87%
“…The extract of L. littorea leaves from Malaysia was reported to possess anti-microbial potential [29]. The leaf n-hexane extract of this species yielded triterpenes and sterols [30] whereas the twigs of L. littorea were described to contain macrocyclic lactones (represented by corniculatolide derivatives) and 6,7-dimethoxycoumarin [31].…”
Section: Introductionmentioning
confidence: 99%
“…[54] Compounds isolated from twigs of the plant (myrcetin and 12-hydroxycorniculatolide A) also showed moderate activity against S. aureus. [55] Significant antimicrobial activities were observed by the methanol, [56] acetone, [57] aqueous, [27] and ethanol extracts of the leaves and stem of Heritiera fomes along with the zinc and silver nanoparticles isolated from the bark. [4] Several studies were made on the antimicrobial potential of various extracts and their fractions from the leaf, [58] stem, [59] pneumatophores, [60] root, [61] and bark [62] of Excoecaria agallocha.…”
Section: Raimentioning
confidence: 99%
“…In addition, the pure compounds of macrocyclic lactone and coumarin derivatives from the twig of L. littorea could scavenge free radicals because their structures contained many conjugated double bonds and oxygen as a substituent group, resulting in highly efficient free radical capture with lower IC50 values. 14 To increase the understanding of the antioxidant effect of methanol extracts of L.littorea bark, flower, leaf and twig, their phenolic and flavonoid compounds should be isolated and purified in future studies.…”
Section: Antioxidant Activitymentioning
confidence: 99%